1992
DOI: 10.1055/s-0038-1646310
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic Potential and Antiphospholipid Antibodies in Systemic Lupus Erythematosus and Other Connective Tissue Disorders

Abstract: SummaryWe studied the fibrinolytic response before and after venous occlusion (VO) in 30 patients with systemic lupus erythematosus (SLE), 25 with rheumatoid arthritis (RA) and 25 with different connective tissue disorders. Results were compared in patients with and without antiphospholipid antibodies (APA) and a history of either thrombosis or abortions. Before occlusion plasma levels of tissue-type plasminogen activator (t-PA) antigen and its inhibitor (PAI-1) were significantly higher in the patient group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…The same authors suggested that in these patients the occurrence of abortions might be linked to the PAI-1 increase. Also in patients without SLE, the presence of aPL was associated with hypofibrinolysis due to high PAL1 levels [34,49]. However, data on fibrinolytic parameters in patients with antiphospholipid antibodies have given contradictory results [33-351.…”
Section: Discussionmentioning
confidence: 97%
“…The same authors suggested that in these patients the occurrence of abortions might be linked to the PAI-1 increase. Also in patients without SLE, the presence of aPL was associated with hypofibrinolysis due to high PAL1 levels [34,49]. However, data on fibrinolytic parameters in patients with antiphospholipid antibodies have given contradictory results [33-351.…”
Section: Discussionmentioning
confidence: 97%
“…IgG containing aCL bound to cultured endothelial cells in the presence of b 2 -GPI, and induced cell adhesion molecules such as E-selectin, vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) [56], which may lead to a procoagulant state. It is also known that aPL induce procoagulant substances such as tissue factor [57,58], plasminogen activator inhibitor-1 [59] and thromboxane A2 [60], in which processes aPL are likely to affect cells via b 2 -GPI or other phospholipid-binding proteins [61]. In terms of the binding mechanism of aPL, the binding of aCL to protein C with a combination of phospholipids and b 2 -GPI might be a similar phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas there is general consensus that plasminogen activator inhibitor-1 (PAI-1) [18,[21][22][23][24] and PAI-1/t-PA ratios [25] are increased, there is conflicting evidence on the plasma levels of other fibrinolysis proteins such as t-PA, which has been reported to be variable in SLE patients [20][21][22][26][27][28][29]. Furthermore, the role of TAFI in SLE has yet to be fully evaluated.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, impaired fibrinolytic activity has been suggested to be a contributing factor for increased thrombotic events in patients with SLE; however, the exact cause(s) remains unclear [17][18][19][20][21][22]. Whereas there is general consensus that plasminogen activator inhibitor-1 (PAI-1) [18,[21][22][23][24] and PAI-1/t-PA ratios [25] are increased, there is conflicting evidence on the plasma levels of other fibrinolysis proteins such as t-PA, which has been reported to be variable in SLE patients [20][21][22][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%